Agro-Ecological Management of Coffee Pests in Brazil - Venzon, Madelaine (Frontiers in Sustainable Food Systems, 2021)
Coffee plants host several herbivorous species, but only few are considered pests. Brazil is the largest world coffee producer, and the two key coffee pests of the crop in the country are the coffee leaf miner Leucoptera coffeella and the coffee berry borer Hypothenemus hampei. However, in some regions or on specific conditions, species of mites and scales can also cause damage to coffee plants. Conventional management of coffee pests relies on chemical pesticides, and it is the most common used strategy in Brazil, but environmental problems, pest resistance and toxicity related issues have led coffee growers to search for alternatives for pest control. Agro-ecological strategies suitable to coffee cultivation can be adopted by farmers, based on plant diversification, in order to provide resources for natural enemies, such as nectar, pollen, shelter, microclimate conditions and oviposition sites, thereby promoting conservation biological control. Here, I revise these strategies and report the results from research in Brazil. I include results on agroforestry, use of cover crops, and non-crop plant management. These are complemented by curative measures based on the use of organic farming approved pesticides that can be employed when the agro-ecological practices are not yet consolidated. I also present the cultural control method used for several coffee producers in Brazil to decrease coffee berry borer damage.